Paciente femenino de 8 años de edad con diagnóstico de asma bronquial. - Cruz Estrella, Jackeline Luciana (2021)
Bronchial asthma is one of the diseases in whose pathogenesis various cells and mediators of inflammation intervene, conditioned in part by genetic factors and that presents with bronchial hyperresponsiveness and a variable obstruction to airflow, totally or partially reversible, either by the action medicated or spontaneously. With regard to Ecuador, the Ecuadorian Institute of Statistics and Censuses (INEC) maintains that in 2010 3,275 cases of this disease were registered. We present the case of an 8-year-old female patient, schoolboy, with a family pathological history of bronchial asthma, who comes accompanied by a mother who refers to a clinical picture of 24 hours of evolution, characterized by non-productive, non-cyanozant, non-productive cough. rubicundizing, non-emetizing, hyaline rhinorrhea and 3 hours ago data of tachypchene, mid and low subcostal retractions were added. M Through the tests carried out and the support of oxygen support, the diagnosis of bronchial asthma was reached, the same that was decided to be hospitalized with a stay of 5 days and treated with Salbutamol 100mg 2 puff C / 4h with aerochamber, Ipratropium bromide 2 puff C / 6h with air chamber, fluticasone + salmeterol 125 / 25mcg 2 puff every 12h with air chamber, methylprednisolone 2mg / kg / dose IV every 6h Magnesium sulfate 50mg / mg / kg / dose IV every 8h. The case is presented below, along with a review on bronchial asthma